Basic data about the synanthropic flora of the territory of “Tuzlоvski lymany” National park (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Territory of the National park “Tuzlovski lymany”, in our view, is rather strongly transformed. Therefore, at the study of this territory flora we paid the special attention to the presence of synanthropic species of higher vascular plants. By results of primary researches, 149 species of synanthropic plants were found which make 52,28 % from the common amount of species of Park flora. The most species are alien fraction. The most of alien plants are epecofytes. Distributing of species from fraction is more even. For the separate floras of estuaries coast there is the substantial varying of synanthropic species amont. Prevailing of alien fraction species is also observed. The list of the found types of plants with high invasion ability is given.
Keywords: National park “Tuzlovski lymany”, synanthropic species, invasion species of plants.